The Influence of E-Wom, Live Streaming, and Influencer Marketing on Repurchase Intention of Skincare in Tiktok Shop Through Brand Trust (Consumer Study) Skintific in Padang City) - Sofia Sofia; Fitria Ridhaningsih (International Journal of Economics and Management Research, 2025)
Skintific is a skincare product marketed through the TikTok Shop digital platform and has experienced rapid growth in the beauty industry in Padang City. This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), Live Streaming, and Influencer Marketing on the intention to repurchase Skintific products, as well as the role of Brand Trust as a mediating variable. The method used is a quantitative approach with survey techniques and Partial Least Square (PLS) analysis of Skintific consumers. The results of the study show that E-WOM, Live Streaming, and Influencer Marketing have a positive influence on the intention to repurchase Skintific products. In addition, Brand Trust plays an important role as a mediator that strengthens the relationship between the three variables and the intention to repurchase. An effective marketing strategy requires selectivity in choosing credible influencers, maintaining transparency in brand communication, and maintaining product quality to increase consumer trust. In conclusion, increasing the intention to repurchase Skintific products on TikTok Shop can be achieved by strengthening Brand Trust by optimizing E-WOM, Live Streaming, and Influencer Marketing..